The Impact of TikTok-Based Digital Marketing on Consumer Purchase Intention: Evidence from Greenhouse Tanjoeng Farm in the Perspective of Islamic Economics - Ridho Muhammad Rizqi; Desy Bariyyatul Qibtiyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The rapid growth of social media has transformed digital marketing practices, making TikTok one of the most influential platforms in shaping consumer purchase intention. This study examines the effects of promotion, content attractiveness, and consumer trust on purchase intention through TikTok marketing from the perspective of Islamic economics. A quantitative approach was employed using data collected from 150 consumers of Greenhouse Tanjoeng Farm and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that content attractiveness and consumer trust positively influence purchase intention, whereas promotion does not have a significant effect. These results indicate that consumers in digital environments place greater emphasis on engaging content, credibility, and trustworthy relationships than on conventional promotional activities. From the perspective of Islamic economics, the findings reinforce the importance of tabligh, fathanah, amanah, and shiddiq as ethical foundations for digital marketing practices. This study contributes to the literature by demonstrating that the effectiveness of TikTok marketing depends primarily on content quality and consumer trust rather than promotional intensity. Practically, the findings provide insights for businesses to develop ethical, trust-based, and content-oriented marketing strategies to enhance consumer purchase intention in digital marketplaces